TRPV4 activation in Schwann cells mediates mechanically induced pain of oral cancer - Mulpuri, Yatendra; Tu, Nguyen H.; Inoue, Kenji; Harden, Grace; Nicholson, Samuel J.; Seenauth, Anisa; Huang, Yan; Escobar, Keylin G.; Moayedi, Yalda; Bunnett, Nigel W.; Albertson, Donna G.; Schmidt, Brian L. (Frontiers in Pain Research, 2025)
IntroductionPatients with oral cancer often experience intense functional pain due to mechanical stimulation at the cancer site. The role of mechanosensitive ion channels in oral cancer pain, such as TRPV4, is not fully understood.ObjectivesOur objective was to investigate the role of Schwann cell TRPV4 in oral cancer pain.MethodsWe examined the impact of TRPV4 inhibition on oral cancer pain in NU/J and C57BL/6J mice injected with human tongue cancer cell line (HSC-3) and mouse oral cancer cell line (MOC2) in the hind paw or tongue. Mechanical and heat sensitivity were assessed using the von Frey and Hargreaves tests, respectively. TRPV4 expression and functional activity in Schwann cells were analyzed using immunohistochemistry, qRT-PCR, Ca2+ imaging, and patch-clamp electrophysiology. The effect of TRPV4 activation on Schwann cell responses to mechanical stimulation was evaluated using a piezo stimulator. Conditioned media (CM) from TRPV4-activated Schwann cells were injected into the mouse paw to evaluate the contribution of TRPV4 in Schwann cells to mechanical hypersensitivity.ResultsTRPV4 inhibition reduced paw cancer mechanical nociception in mice dose-dependently without affecting heat sensitivity. TRPV4 inhibition also decreased facial nociception in tongue cancer mice. TRPV4 was expressed mainly on the plasma membrane of mouse Schwann cells and activation of TRPV4 induced Ca2+ responses and whole-cell membrane currents in human Schwann cells. Mechanoactivated currents in human Schwann cells were inhibited by the TRPV4 antagonist HC-067047. Schwann cell CM induced mechanical hypersensitivity in mice, which was blocked by pre-treatment with HC-067047.ConclusionTRPV4 activation plays a role in mediating mechanically induced pain of oral cancer.